General Reports of the XXth General Congress of the International Academy of Comparative Law - Rapports généraux du XXème Congrès général de l'Académie internationale de droit comparé - Boele-Woelki, Katharina; Fernández Arroyo, Diego P.; Senegacnik, Alexandre (Rapports généraux de l'AIDC / General Reports of the IACL ;, 2021)
X, 709 p.